Insulin Sensitivity Following Exercise Interventions: Systematic Review and Meta-Analysis of Outcomes Among Healthy Adults - Conn, Vicki S.; Koopman, Richelle J.; Ruppar, Todd M.; Phillips, Lorraine J.; Mehr, David R.; Hafdahl, Adam R. (Journal of primary care & community health, 2014)
Objective: Although exercise can improve insulin sensitivity, no adequate synthesis exists of exercise intervention studies with regard to their effect on insulin sensitivity. This comprehensive meta-analysis synthesized the insulin sensitivity outcomes of supervised exercise interventions. Method: Extensive literature searching located published and unpublished intervention studies that measured insulin sensitivity outcomes. Eligible studies tested supervised exercise interventions among healthy adults. Primary study characteristics and results were coded. Random-effects meta-analyses of standardized mean differences included moderator analyses. Results: Data were synthesized across 2509 subjects (115 samples, 78 reports). The overall mean effect size for 2-group postintervention comparisons was 0.38 (95% confidence interval [CI] = 0.25-0.51, I2 = 0%) and for 2-group pre–post comparisons was 0.43 (95% CI = 0.30-0.56, I2 = 52%; higher mean insulin sensitivity for treatment than control subjects). The postintervention mean of 0.38 is consistent with treatment subjects ending studies with a mean fasting insulin of 6.8 mU/L if control participants’ mean fasting insulin were 7.9 mU/L. Exploratory moderator analyses did not document different insulin sensitivity effect sizes across intervention characteristics or sample attributes. Conclusion: This study documented that exercise is a valuable primary care and community health strategy for healthy adults to improve insulin sensitivity and lower the risk for diabetes conferred by insulin resistance.